State of Training, Clinical Services, and Research on Dual Disorders Across France, India, Israel, and Spain. Issue 3 (1st October 2016) - Balhara, Yatan Pal Singh; Lev-Ran, Shaul; Martínez-Raga, José; Benyamina, Amine; Singh, Shalini; Blecha, Lisa; Szerman, Nestor
ABSTRACT: Objective: This article overviews training, clinical services, and research on dual disorders across four countries: France, India, Israel, and Spain.Methods: The current dual disorders systems in each of the four countries were reviewed, with a focus on strengths and limitations of each.Results: In France, psychiatric care occurs within the public health care system and involves little training of medical graduates for managing dual disorders. Special courses and forums for specialists have recently started to meet the growing interest of physicians in learning how to manage dual disorders. The Indian health care system grapples with a large treatment gap for mental disorders, and while some treatment services for dual disorders exist, specific research and training efforts on dual disorders are just beginning. Israel has both public- and private sector services for patients with dual disorders, with specialized inpatient and emergency care for the acutely ill as well as day care and therapeutic communities for long-term management. Interest by researchers is growing, but training and education efforts in dual disorders are, however, minimal. Similar to the other countries, addiction and psychiatry disciplines are governed by separate divisions within the National Health System in Spain. There are some dual disorders services available, but they are limited in scope. While medical professionals clearly recognize the importance of dual disorders, there is no such recognition by the national and regional governing bodies.Conclusions: The common thread in various aspects of dual disorder management in each of these four countries is that there is a lower-than-desirable level of attention to dual disorders in terms of care, policy, research, and training. There are growing opportunities for training and continuing education in dual disorders management. We suggest that nations could learn from each other's experiences on how to address the issue of dual disorders.